ELDERLY SPORTING PREFERENCE ON ORGANIZATION OF 3RD AGE EVENTS (Fiep Bulletin - online, 2013)
The aim of this work is to evaluate the opinion of elderly to develop an event for people of 3rd age in Santa Catarina state. 69 elderly participate of this research (35 male and 34 female), that came from 39 different cities. The volunteers answered a survey with personal details and sportive preferences. Their opinion was organized on  Microsoft Excel 2007 for Windows® sheets and served as a basis to what be developed on “Jogos Abertos da Terceira Idade (JASTI)” that initially counts with canasta, bocce, ninepin bownling, domino and dance modalities. At 3rd edition it was included truco. It is possible to observe along prior editions of this event there was strong participation and at most recently editions it was necessary to realize regional classificatory stages.Knowing the benefits of physical activity related to quality of life, healthy life style maintenance and sociability aspects of elderlies, it was suggested the realization of sportive events exclusively to this parcel of population and that be made to guide public politics for 3rd age and adequacy of the events for their cultural features.
Keywords: Elderly; Quality of life; Event organization.